STUDI KEDALAMAN GERUSAN LOKAL PADA PILAR JEMBATAN SIMPANG SURABAYA KRUENG ACEH, BANDA ACEH - Eldina Fatimah (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2013)
Simpang Surabaya Bridge positioned at coordinates 5033'38” LU and 95019'4,1'' BT is located at Kuta Alam sub-district of Banda AcehMunicipality. The bridge was built across the river Krueng Aceh with ± 100 meters long with pillars to support the bridge. Pillars were in the river, resulting in narrowing the river cross section that led to disturbing river flow. Changes in flow velocity caused a scour around the pillars, so it is necessary to study local scour depth on the pillars. There are two types of pillars that existed. One type is located at the upstream side with Cylinder Group-shaped pillars (circular combination type) having the width of one meter and four meters long, while at the downstream part, the pillar type is round pillar-shaped nose with the width and length of one meter and three meters respectively. The aim of this research is to determine the scouring effect on the pillars based on data taken in 2008 and data from current measurement. While theactual local scour depth around the pillars were measured using instrument Qliner where the river was divided into two meters wide per section.Measurement data then is shown in the form of contour and cross section. From field measurement, it is found that the scouring depth at the upstream of the pillar is 0.88m whereas sedimentation occurred at the downstream part of the pillar. By using the measurement data on 2008 and compared with the meassured data, it is found that the Simpang Surabaya pillars were scoured noticeably and need to be protected. From the calculation, the pillars should be protected using riprap with a diameter of 0.945 meters.